ӘЖИНИЯЗ ШЫҒАРМАЛАРЫНДА ҚОЛЛАНЫЛҒАН ФИТОНИМЛЕР ҲАҚҚЫНДА - Қарлыбаева, Г.; Өтемисов, Ә. (FAN va JAMIYAT, 2016)
The article deals with the names of plants in the work of the great Karakalpak poet of the XIX century Ajiniyaz and their direct and indirect usages. Their semantic peculiarities were analyzed on concrete examples.